Algorithm of Lecturer’s Activity in Formation of Students’ Foreign Language Communicative Competence - A. I. Sorokina (Наука и техника)
The paper is devoted to a problem pertaining to formation of foreign language communicative competence among students, economists-to-be, as a component part of their professional competence.